2014
DOI: 10.1002/adfm.201304270
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Realization of Phase/Size Manipulation, Upconversion Luminescence Enhancement, and Blood Vessel Imaging in Multifunctional Nanoprobes Through Transition Metal Mn2+ Doping

Abstract: A strategy is demonstrated for simultaneous phase/size manipulation, multicolor tuning, and remarkably enhanced upconversion luminescence (UCL), particularly in red emission bands in fi xed formulae of general lanthanidedoped upconverting nanoparticles (UCNPs), namely NaLnF 4 :Yb/Er (Ln: Lu, Gd, Yb), simply through transition metal Mn 2+ -doping. The addition of different Mn 2+ dopant contents in NaLnF 4 :Yb/Er system favors the crystal structure changing from hexagonal (β) phase to cubic (α) phase, and the cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
106
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 223 publications
(115 citation statements)
references
References 54 publications
2
106
2
Order By: Relevance
“…It can be observed that the FIR value increased gradually with increasing the temperature and reached its maximum value at 553 K. The experimental data can be well fitted with Eq. (1) and the values of coefficient and energy gap were found to be $ 6.67 and 706.68 cm À 1 , respectively. For optical thermometry applications, the sensing sensitivity was estimated from the equation of S ¼ dR/dT ¼ R(ΔE 12 /kT 2 ) [23,24].…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…It can be observed that the FIR value increased gradually with increasing the temperature and reached its maximum value at 553 K. The experimental data can be well fitted with Eq. (1) and the values of coefficient and energy gap were found to be $ 6.67 and 706.68 cm À 1 , respectively. For optical thermometry applications, the sensing sensitivity was estimated from the equation of S ¼ dR/dT ¼ R(ΔE 12 /kT 2 ) [23,24].…”
Section: Resultsmentioning
confidence: 95%
“…Over the past decade, enormous interest in rare-earth (RE) ions doped materials has been gained owing to their wide applications in luminescent label for bioimaging, color displays, white lightemitting diodes, etc [1][2][3]. Some interesting phenomena, such as enhanced piezoelectricity, photoluminescence (PL), and upconversion (UC) emission, were observed in RE ions doped ferroelectric ceramics [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…S12a-h), even when there were as many as 209 points (detail data are listed in Table 3). Since lanthanide complexes have many applications in bio-labeling, bio-imaging and photodynamic therapy, the property of timer may enhance the potential application of lanthanide complexes in the field of online bio-monitoring, protein tracking or biomarkers [50,51].…”
Section: Tablementioning
confidence: 99%
“…The quenching effect of Mn 2þ ions is probably ascribable to the depopulation of nonradiative energy transfer from the Er 3þ to Mn 2þ ( 2 H 9/2 / 4 S 3/2 / 4 T 1 ), especially at high doping concentration of Mn 2þ ions [72]. In our study, we find that the largest emission intensity can be achieved when UCNPs doping 2.5% Mn 2þ ions, the emission intensity of which is 1.49 times than that of undoped UCNPs [39,43,60,63]. And the red to green intensity ratio (I R /I G ) increases from 3.42 to 3.97.…”
Section: Structure Morphology and Luminescent Properties Of Uchns-pamentioning
confidence: 41%